Eye Movement Patterns in Solving Science Ordering Problems - Hui Tang; Elizabeth Day; Lisa Kendhammer; James N Moore; Scott A Brown; Norbert J Pienta (Bern Open Publishing, 2016)
Dynamic biological processes, such as intracellular signaling pathways, commonly are taught in science courses using static representations of individual steps in the pathway. As a result, students often memorize these steps for examination purposes, but fail to appreciate either the cascade nature of the pathway. In this study, we compared eye movement patterns for students who correctly ordered the components of an important pathway responsible for vasoconstriction against those who did not. Similarly, we compared the patterns of students who learned the material using three dimensional (3-D) animations previously associated with improved student understanding of this pathway against those who learned the material using static images extracted from those animations. For two of the three ordering problems, students with higher scores had shorter total fixation duration when ordering the components and spent less time (fixating) in the planning and solving phases of the problem-solving process. This finding was supported by the scanpath patterns that demonstrated that students who correctly solved the problems used more efficient problem-solving strategies.